Is it Profitable to Compete for the Elite of the Brazilian Championships? - Thiago Bruno de Jesus Silva; Leandro Dias Catellan Teixeira; Rodrigo Rengel; Ronan Reis Marçal3 (Universidade Salgado de Oliveira, 2021)
This study aims to verify if it is profitable to play in the first division and if all clubs in the second division should aspire to move up. The population of this research refers to the 20 clubs from the B series of the Brazilian Football Championship during the exercises of 2017, 2018 and 2019. The research adopted quantile regression as a technique. As a result, there is the influence of the independent variable access on the variation of the dependent variable gross revenue of clubs - in a positive way. The theoretical implication is to investigate the reality of clubs in the second division. In the practical field, one can see the importance of increasing the revenues of clubs in the second division so that clubs are more financially balanced, the construction of competitiveness between clubs and, consequently, a more attractive first division. Clubs will not feel compelled to aspire to the first division at any cost, which can lessen risky financial behavior